2020
DOI: 10.1042/bst20190233
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the importance of individual mitochondrial genotype in susceptibility to drug-induced toxicity

Abstract: The mitochondrion is an essential organelle responsible for generating cellular energy. Additionally, mitochondria are a source of inter-individual variation as they contain their own genome. Evidence has revealed that mitochondrial DNA (mtDNA) variation can confer differences in mitochondrial function and importantly, these differences may be a factor underlying the idiosyncrasies associated with unpredictable drug-induced toxicities. Thus far, preclinical and clinical data are limited but have revealed evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 72 publications
(101 reference statements)
0
16
0
Order By: Relevance
“…Several studies have indicated that the mitochondrial genome may be a factor in the onset of adverse drug reactions, including those associated with linezolid and streptomycin (Chen et al 2007 ; Pacheu-Grau et al 2012 ; Penman et al 2020 ). In addition, drug-induced mitochondrial dysfunction is an important part of preclinical screening in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that the mitochondrial genome may be a factor in the onset of adverse drug reactions, including those associated with linezolid and streptomycin (Chen et al 2007 ; Pacheu-Grau et al 2012 ; Penman et al 2020 ). In addition, drug-induced mitochondrial dysfunction is an important part of preclinical screening in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large inter-individual variation in mtDNA copy number, and while the origin of this variation is still unknown, low mtDNA levels could present a risk factor for the mitochondrial toxicity of drugs known to interfere with mtDNA [ 6 ]. In addition, variations and mutations in mtDNA represent an important inter-individual difference associated with adverse drug reactions and idiosyncratic DILI [ 158 , 159 ]. Emerging studies have shown that mitochondrial genetics and specific mtDNA haplogroups are involved in increased susceptibility to drug toxicity, especially for toxicity induced by antibiotics, antiretrovirals and chemotherapeutic agents [ 159 ].…”
Section: Factors Influencing Drug-induced Hepatic Mitochondrial Dysfu...mentioning
confidence: 99%
“…In addition, variations and mutations in mtDNA represent an important inter-individual difference associated with adverse drug reactions and idiosyncratic DILI [ 158 , 159 ]. Emerging studies have shown that mitochondrial genetics and specific mtDNA haplogroups are involved in increased susceptibility to drug toxicity, especially for toxicity induced by antibiotics, antiretrovirals and chemotherapeutic agents [ 159 ].…”
Section: Factors Influencing Drug-induced Hepatic Mitochondrial Dysfu...mentioning
confidence: 99%
“…Limited information, however, is available about the roles of mitochondrial haplogroups in susceptibility to drug-induced toxicity. Anti-retroviral therapy (ART), antibiotics and chemotherapeutic agents are well known drug classes in relation to the mitochondria mediated drug toxicities [ 7 ]. The mtDNA mutations and copy numbers have been proposed as potential biomarkers to monitor therapeutic responses and prognosis in cancer treatments, although the mechanisms are not well established [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%